2009
DOI: 10.1242/jcs.049734
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular growth factors and mitogens cooperate to drive mitochondrial biogenesis

Abstract: Cells generate new organelles when stimulated by extracellular factors to grow and divide; however, little is known about how growth and mitogenic signalling pathways regulate organelle biogenesis. Using mitochondria as a model organelle, we have investigated this problem in primary Schwann cells, for which distinct factors act solely as mitogens (neuregulin) or as promoters of cell growth (insulin-like growth factor 1; IGF1). We find that neuregulin and IGF1 act synergistically to increase mitochondrial bioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 61 publications
(85 reference statements)
2
27
0
Order By: Relevance
“…The “confocal pinhole”, an aperture placed in front of the detector that rejects out of focus light and gives confocal microscopy its name, allows images to be taken at different depths through the sample [144]. Following this “optical sectioning”, the slices can be reconstructed into a three-dimensional image, permitting the full spatial organisation of the mitochondrial network inside a live cell or tissue to be characterised [145].…”
Section: Practical Application Of Live-cell Nad(p)h Fluorescencementioning
confidence: 99%
“…The “confocal pinhole”, an aperture placed in front of the detector that rejects out of focus light and gives confocal microscopy its name, allows images to be taken at different depths through the sample [144]. Following this “optical sectioning”, the slices can be reconstructed into a three-dimensional image, permitting the full spatial organisation of the mitochondrial network inside a live cell or tissue to be characterised [145].…”
Section: Practical Application Of Live-cell Nad(p)h Fluorescencementioning
confidence: 99%
“…Long-time exposure of cells to BrdU (i.e. 18-24 h) is generally used to detect full mtDNA replication (Echave et al, 2009). Short-time exposure to the drug was tested here to assess the kinetics of mtDNA replication, and early replication events.…”
Section: Mtrip Exposes Mtdna Initiation Of Replicationmentioning
confidence: 99%
“…Indeed, currently available fluorescence in situ hybridization (FISH) tools including recent improvements (Alán et al, 2010;Ozawa et al, 2007), are not fit to identify mitochondria engaged in DNA replication, and to discriminate distinct transcription profiles of the organelles. Conversely, incorporation of bromodeoxyuridine (BrdU) may label a large fraction of organelles (Echave et al, 2009), cumulating replication events that started at different times, and thereby limiting the informative potential on mtDNA replication dynamics within the mitochondrial population. Importantly, higher resolution studies have recently shown that replication of mtDNA occurs only in a subset of nucleoids (Kukat et al, 2011), underscoring the need of understanding the properties of mitochondrial replication dynamics in single cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not surprising that mitochondrial function is tightly controlled by cytokines/growth factors to meet diverse energy demands [18][19][20][21] . Nevertheless, mechanistic studies are required to understand how cytokines/growth factors integrate the regulation of mitochondrial and cellular functions, and to determine their physiological and pathological significance at the whole-organism level.…”
mentioning
confidence: 99%